2009
DOI: 10.2174/1874210600903010147
|View full text |Cite
|
Sign up to set email alerts
|

Benign Oral Masses in a Northern Jordanian Population-a Retrospective Study

Abstract: The aim of this study was to evaluate the relative frequencies, types and distribution of benign oral masses in North Jordanians. The records of the Department of Pathology at Jordan University of Science & Technology were reviewed and analyzed for patients with benign oral soft tissue masses, received during an 11-year period (1991-2001). The main outcome measures were patients’ age and sex, and the mass type and location. A sum of 818 benign oral soft tissue masses (4% neoplastic and 96% non-neoplastic) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
26
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 17 publications
(28 reference statements)
16
26
1
Order By: Relevance
“…Males and females were equally affected, whereas female predominance was observed by Carneiro et al . The tongue was predominantly affected, which is in accordance with previous studies .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Males and females were equally affected, whereas female predominance was observed by Carneiro et al . The tongue was predominantly affected, which is in accordance with previous studies .…”
Section: Discussionsupporting
confidence: 91%
“…Many studies on the prevalence of benign orofacial tumors have been reported from other countries . Nevertheless, a single study from the eastern province of Saudi Arabia reported the prevalence of these tumors, along with other oral and maxillofacial pathologies .…”
Section: Introductionmentioning
confidence: 99%
“…Fibroepithelial polyp was particularly common, representing 12% of the entire sample. It was seen most commonly in the fifth decade of life, mainly in female subjects and located most often on the buccal mucosa, which is in accordance with data in the literature.…”
Section: Discussionsupporting
confidence: 90%
“…The most common autoimmune lesion was Sjögren's syndrome ( n = 18), which was more prevalent in female patients, in accordance with the literature. The elevated number of cases of this lesion on the labial mucosa reflects the most common site for minor salivary gland biopsies.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, distinction between the benign and malign lesions is crucial for the further prognosis and treatment[2]. …”
Section: Introductionmentioning
confidence: 99%